Lycopene improves activation of antioxidant system and Nrf2/HO-1 pathway of muscle in rainbow trout (Oncorhynchus mykiss) with different stocking densities - Şahin, Kazım; Orhan, Cemal; Yazlak, Hasan; Tuzcu, Mehmet; Şahin, Nurhan (Elsevier, 2014)
The purpose of this study was to describe the effect of lycopene on antioxidant status, heat shock protein 70 (Hsp70), nuclear factor (erythroid-derived 2)-like 2 (Nrf2) and heme-oxygenase 1(HO-1) levels in the muscle of rainbow trout (Oncorhynchus mykiss). The fish were kept at low(20 kg m(3 - 1)) or high(100 kg m(3 - 1)) stocking densities till the end of study and fed a basal diet or the basal diet supplemented with either 200 or 400 mg of lycopene kg(-1) of diet. The protein, lipid and ash contents in the muscle were not changed by the supplementation of lycopene in rainbow trout kept under high or low stocking densities. In response to increasing supplemental lycopene level, there were linear increases in lycopene levels, superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GSH-Px) activities (P < 0.001) and Nrf2 and HO-1 levels of muscle; linear decreases in muscle malondialdehyde (MDA) and Hsp70 levels (P < 0.001). In conclusion, lycopene supplementation to fish reduces the detrimental effects of oxidative stress and lipid peroxidation resulting from stocking densities via activating host defence system at cellular level. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Lycopene; Lipid peroxidation; Stocking density; Trout